Urban sociolinguistics the city as a linguistic process and experience - Smakman, Dick 1970-; Heinrich, Patrick (Routledge, 2018)
"Providing new perspectives on crucial themes such as language choice and language contact, code-switching and mixing, language and identity, language policy and planning and social networks, this is key reading for students and researchers in the areas of multilingualism and super-diversity within sociolinguistics, applied linguistics and urban studies."--Provided by publisher.